ENHANCING CRITICAL THINKING IN SPEAKING SKILL THROUGH SEKAWAN-P - Diani Nurhajati; Kencanawati, Dewi; Riwayatiningsih, Rika (Universitas Nusantara PGRI Kediri, 2020)
There are some problems in teaching English faced the high school many teachers and students. Based on the observation in one of good senior high schools, it was found out some weaknesses in teaching English. The teaching process relied on the exercises in the student book. The teaching activity was more teacher center. The teacher never made development on the materials, which were more challenging. As a result, the students were not trained to have critical thinking. This could be seen when the teacher asked questions, they answered using short answer, without any elaboration. This influences the ability of their critical thinking. Actually, graduates of high schools should be equipped with skills to face the Industrial era 4.0. The skills are Critical Thinking, Creativity, Collaboration, and Communication. All teachers can train those skills when they teach, including English teachers. Therefore, this research aims at describing how the teaching model Sekawan-P can enhance the students’ critical thinking in speaking skill. The study was a Lesson Study (LS) program between an English teacher of SMAN 1 Kediri and three lecturers of Nusantara PGRI Kediri University. They worked together to solve the problems mentioned above using this teaching model. They revised the existing lesson plan and materials, made improvement, and revised the teaching plan. The results show that after they applied Sekawan-P, the critical thinking of the students developed. It can be seen on how they delivered their arguments in speaking skill.